Prospective comparative study of patients with culture proven and high suspicion of adult onset septic arthritis. Issue 4 (1st April 2003) - Gupta, M N; Sturrock, R D; Field, M
Abstract : Objective: To investigate whether patients with acute septic arthritis (SA) diagnosed by positive synovial fluid (SF) culture (Newman grade A) have different clinical and serological features from those with sterile SF in whom there is nonetheless a high suspicion of SA (Newman grades B and C). Patients and methods: A prospective 12 month multicentre hospital based study of adult patients with SA recruited 47 patients with culture positive SA and 35 patients with clinically suspected SA but sterile SF. Results: Patient demography, clinical and laboratory features at presentation were similar irrespective of the underlying diagnosis, SF culture, and the presence of prosthetic joints. Medical and surgical treatment and outcome were comparable in the two patient groups. Patients with both suspected and proven SA were more likely to be from the more socially deprived areas of our community (p<0.0001). Conclusion: Patients in whom there is a high clinical suspicion of SA are comparable to those patients with SA with a positive SF culture and have similar morbidity and mortality on follow up. Therefore, if clinical suspicion of SA is high then it is correct to treat as SA in the absence of bacterial proof.